Reassessing the Role of Shared Mobility Services in a Transport Transition: Can They Contribute the Rise of an Alternative Socio-Technical Regime of Mobility? - Lisa Ruhrort (Sustainability, 2020)
Recent years have seen a proliferation of platform-based “shared mobility services” (SMS) such as car-, bike-, and e-scooter-sharing in many cities in Germany and around the world. At the same time, these services have become the subject of intense debates: Are they replacing private car travel, thus contributing to sustainable mobility in cities? Or are they drawing users away from public transit and cycling while obstructing public space? From the perspective of sustainable mobility politics, it seems far from clear which role these new services could play in transitioning to a less car-centric mobility system. While a number of potential effects and ensuing governance issues of shared mobility services (e.g., regarding questions of equitable access, data governance, the role of public versus private actors) have already been studied, this article explores the role of shared mobility services (SMS) in triggering system dynamics and feedback loops in the context of sustainability transitions. The article connects questions regarding the sustainability effects of “shared mobility services” with the role of “push” measures to reduce private car traffic in cities. Using a theoretical framework from socio-technical transitions research and from the sociology of technology, it describes the recent growth of shared mobility services in Berlin as an example of the upscaling dynamics of socio-technical niche innovations. Drawing on a series of workshops with mobility service providers and representatives of public authorities, it analyses the potential for conflict as well as for coalition-building between service providers and public authorities. Based on the theoretical concept of the role of feedback loops and windows of opportunity for transitions, it shows how the market growth of shared mobility services has added momentum to an already ongoing political debate over the legitimate use of public space in Berlin. Against this backdrop, the article discusses how growing numbers of car-, bike-, and e-scooter-sharing vehicles could open up windows of opportunity for re-distributing space away from private cars. The article concludes that supporting and regulating SMS will be key to steering their growth in the direction of sustainability.
Additional information: APC was funded by the WZB and the Open Access fund of the Leibniz Association.
Keywords: 300; transport policy; sustainable mobility; shared mobility services; multi-level perspective; socio-technical systems